Congruency of gaze metrics in action, imagery and action observation - Causer, Joe; McCormick, Sheree A.; Holmes, Paul S. (Frontiers in Human Neuroscience, 2013)
The aim of this paper is to provide a review of eye movements during action execution, action observation and movement imagery. Furthermore, the paper highlights aspects of congruency in gaze metrics between these states. The implications of the imagery, modeling and action gaze congruency are discussed in terms of motor learning and rehabilitation. Future research directions are outlined in order to further the understanding of shared gaze metrics between overt and covert states. Suggestions are made for how researchers and practitioners can structure action observation and movement imagery interventions to maximize re(learning).